A flexible and scalable Ethernet architecture for telecommunication transport networks. (2018) - Asadujjaman, A.S.M.; Alam, Mohammad Shah
This paper presents a novel wireless channel condition aware and floodless Ethernet architecture for telecommunication carrier networks, namely FFCSEA. The distinct advantages of FFCSEA are: 1) efficiency and resilience for wireless transmission links that are capable of adaptive modulation; 2) scalability of a single Ethernet network for a large number of nodes (i.e., eNodeB); 3) backward compatibility with existing Ethernet technology; 4) fast response time compared to SDN controller based proxy. By introducing multi-instance ITU-T G.8032 (ERPS) ring design and an optimised proactive learning based proxy mechanism, FFCSEA achieves flexibility (i.e., efficiency and resilience during microwave adaptive modulation changes) and scalability of the transport network. Simulation and analytical results validate comparative advantage of FFCSEA over existing protocols both in terms of flexibility and scalability. The analysis and design presented in this paper will be useful for both traditional networks and SDN.